COVID-19 Compulsory Vaccination of Healthcare Workers and the Italian Constitution - Vinceti, S. R. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
On April 1, 2021, the Italian Government issued the Decree Law no. 44 establishing COVID-19 compulsory vaccination for healthcare workers. In covering the news, national and international commentators have foreshadowed controversy over its constitutional status. In fact, it seems sensible to wonder if mandatory vaccination is consistent with the right to medical self-determination in the Italian Constitution, and if vaccine mandates that exclusively apply to a specific part of the population can be squared with its Equality Principle. As it happens, both answers are in the affirmative. On the one hand, the Italian Constitution acknowledges medical self-determination, but it explicitly admits of public health coercive measures, as both the text of the Constitution and its original understanding make abundantly clear. On the other, as to the Equality Principle, the scientific literature has long attested to the unique benefits of vaccinating healthcare workers, which seem all the more appropriate amidst a pandemic. Moreover, the government’s choice of moderate penalties for vaccine refusal and the temporary nature of the mandatory regime further agree with the Italian Constitutional Court’s interpretation of the Equality Principle - the so-called “Reasonableness Criterion.” The Decree Law – meanwhile become, with minor modifications, Law 76 of May 28 2021 - is thus expected to pass foreseeable judicial review. However, it would be beneficial if the Italian government more vocally advocated the constitutionality of its vaccination policies in a general effort to contrast vaccine hesitancy.